PERANAN BMT DALAM PEMBERDAYAAN EKONOMI NASABAH DI KECAMATAN BERASTAGI-KABANJAHE KABUPATEN KARO (STUDI KASUS BMT MITRA SIMALEM AL KAROMAH) - Fauzi Arif Lubis (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2016)
The problem in this research focused on the three aspects, that is: (1) how the customers characteristics which is the empowerment object of BMT Mitra Simalem Al Karomah, (2 empowering forms of what is being done by BMT Mitra Simalem Al Karomah, and (3) how the results of such empowerment. This research is a field research with qualitative approach. The results of this research shows that the customers characteristics of BMT Mitra Simalem Al Karomah can be seen in three aspects, that is: (1) aspects of religion, (2) aspects of business and other work groups, and (3) aspects of the economic level. The economic empowerment that BMT Mitra Simalem Al Karomah done through the realization of financing. Other forms of empowerment that supports are: founding, training and social activities. The research shows that empowerment is successfully done with an indicator of economic development clients and customers active participation which is the object of empowerment. So Empowerment on the social aspects has made the existence of this BMT is quite popular among the public, especially in the District Berastagi and Kabanjahe. Empowerment that performed by BMT Mitra Simalem Al Karomah deemed successful characterized by an increased level of customers economy and the active participation of customers.